Effect of camera position on egocentric localisation with Simulated Prosthetic Vision. (4th February 2021) - Prabhu, Deepa; Wise, Lisa; MacMahon, Clare; De Man, Marten; Petoe, Matthew; McCarthy, Chris
Abstract: Objective:  The positioning of the external camera in current designs of retinal prostheses may affect the egocentric spatial frame of reference and lead to pointing and localisation errors. The present simulated prosthetic vision (SPV) study investigated the immediate effects of four camera positions: (i) centre-mounted (CM), (ii) head-mounted (HM), (iii) left-mounted (LM), (iv) right-mounted (RM) on egocentric localisation. Approach:  Fifteen sighted participants performed a pointing task while viewing the stimulus through a simulation of Bionic Vision Technologies' 44-channel retinal prosthesis. Pointing responses were recorded immediately after exposure to different camera positions and prior to adaptation. The direction and magnitude of pointing errors and associated head movement behaviour were analysed using linear mixed effects analysis. Main results:  Our results showed lower errors for medial camera positions (CM and HM) and overall improved accuracy and precision for CM position. Head orientation was found to largely influence the direction of pointing. There was a high positive correlation between direction of head orientation and direction of pointing with CM and HM camera positions, suggesting medial camera positions facilitated intuitive head orientation cues that are important for reliable egocentric direction estimation. Significance:  The empirical evidence derived from the present SPV study offers practical guidance to reduce the effect on spatial dissociation of camera position in localisation tasks and inform design of future prosthetic vision devices and improve rehabilitation approaches.